Efficacy micro-needling fractional radiofrequency in acne scars - Omer Bin Al-Zou; Asia Hassan Abdulla Saleh; Khaled Husein Algaradi; Fathi Elkasah (Journal of Medical Sciences, 2022)
Background: Acne scars appear most often in people struggling with severe forms of acne vulgaris. Objectives: To determine the efficacy of using microneedles to deliver bipolar radiofrequency energy for treating acne scars. Materials and method: We performed a retrospective review of medical records of Patients diagnosed with acne scars in our clinics in Aden, during the period January 2020 to December 2021. Treatment sessions 4 to 6 and treatment interval one month. Statistical analysis of data was done by estimating rates, means and standard deviations, Fisher test was used and p-value < 0.05 was considered as statistically significant. The statistical software package SPSS version 17 was used. Results: The female patients were (83.3%) and the mean age was 27.8 ± 7.1 years. The difference between age means showed statistically significant (p = 0.000). Boxcar of acne scar were predominant (53.8%). There was a highly statistical significance between values of acne scar types related to sex (p=0.000). Improvement types were marked in (53.8%) patients and distributed as (51.2%) in females and (2.6%) in males, (p=0.001). The most common grade of acne scars were grade IV found in (61.5%) patients, followed by grade III in (30.8%). Marked type improvement found in (53.8%) patients, mild improvements were (12.8%) and moderate types were (33.3%), (p = 0.002). Marked improvement found after 4 sessions in (21.8%) patients. Moderate improvement was in (15.4%) patients after 4 sessions and after 5 sessions was in (11.5%) patients while mild improvement found in (9.0%) patients after 4 sessions, (p > 0.05). Erythema as side effects were in (3.9%) patients, hyperpigmentation found in in (6.4%) patients and edema found also in (2.6%) patients. Conclusion: Fractional radiofrequency is well-tolerated procedure, which can be used for the effective treatment of scarring and it considered as an effective modality of treatment for moderate to severe acne scars.